If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5i + 4)(i + 4) = 0 Reorder the terms: (4 + 5i)(i + 4) = 0 Reorder the terms: (4 + 5i)(4 + i) = 0 Multiply (4 + 5i) * (4 + i) (4(4 + i) + 5i * (4 + i)) = 0 ((4 * 4 + i * 4) + 5i * (4 + i)) = 0 ((16 + 4i) + 5i * (4 + i)) = 0 (16 + 4i + (4 * 5i + i * 5i)) = 0 (16 + 4i + (20i + 5i2)) = 0 Combine like terms: 4i + 20i = 24i (16 + 24i + 5i2) = 0 Solving 16 + 24i + 5i2 = 0 Solving for variable 'i'. Factor a trinomial. (4 + i)(4 + 5i) = 0Subproblem 1
Set the factor '(4 + i)' equal to zero and attempt to solve: Simplifying 4 + i = 0 Solving 4 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + i = 0 + -4 Combine like terms: 4 + -4 = 0 0 + i = 0 + -4 i = 0 + -4 Combine like terms: 0 + -4 = -4 i = -4 Simplifying i = -4Subproblem 2
Set the factor '(4 + 5i)' equal to zero and attempt to solve: Simplifying 4 + 5i = 0 Solving 4 + 5i = 0 Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5i = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5i = 0 + -4 5i = 0 + -4 Combine like terms: 0 + -4 = -4 5i = -4 Divide each side by '5'. i = -0.8 Simplifying i = -0.8Solution
i = {-4, -0.8}
| -4x+4(1-x)=3x+0(1-x) | | 0.6w=0 | | 5p=30-10n | | 4x^2-x=17 | | 7j(8j-1)=0 | | 3x-5(1-x)=-2x+3(1-x) | | 1/5*x=210 | | 10.36+23.199x=56.758 | | (6x+7)(4x+3)=0 | | 3x+21=16x-10 | | 7c^4=-1512c | | -6÷(-3/7) | | -5x-66-6x+30=118 | | 5=-16t^2+26t | | -4x+3(1-x)=-5x+-1(1-x) | | 2x+-4(1-x)=-2x+-2(1-x) | | 96v^2-54=0 | | 2(3x+1)+5-3=x+22+2 | | ((3x/2x-1)-2)/((5/4x)-x/2x-1) | | -121=-y^2 | | (X+4)(x-1)=o | | 2/5a-1-3 | | (5/2)(3/10) | | 2x^2+12+18y^2= | | 0.3z-2=7 | | 25q^2=1 | | 6n=215 | | 3x-5(x+2)=-7 | | 2(2x+x)+10=2(x+10)+18-8 | | 9j(j-7)=0 | | y+2=3434(x+2) | | 8+5y=-22 |